HUBUNGAN PENGETAHUAN, USIA DAN DUKUNGAN SUAMI DENGAN PEMAKAIAN (AKDR) DI PUSKESMAS TELANG JAYA TELANG - Amlah Amlah; Eka Afrika; Wahiro Wahiro (Universitas Pahlawan, 2022)
Contraception is the meeting of a mature egg and sperm cell that results in pregnancy. Contraception is to avoid pregnancy due to the meeting of a mature egg cell with a sperm cell. An estimated 225 million women in developing countries wish to delay or discontinue fertility but do not use any contraceptive method for the following reasons: limited choice of contraceptive method and experience of side effects. Data on the number of active family planning participants in South Sumatra province consisted of IUD 246 people (0.63%), MOW 92 people (0.23%), MOP 116 people (0.29%), condoms 4234 people (10.9%) , Pills 13672 people (35.3%). This research is quantitative using analytical survey research methods, namely correlation analysis research that can be seen how far the contribution of certain factors to the existence of a particular event with the